Stimulation of the Germination and Early Growth of Tomato Seeds by Non-thermal Plasma - Măgureanu, Monica; Sîrbu, R.; Dobrin, Daniela; Gîdea, Mihai (Plasma chemistry and plasma processing, 2018)
The influence of non-thermal plasma on tomato seeds has been investigated using a fluidized bed dielectric barrier discharge generated in air. It was found that plasma-treated seeds germinate faster than untreated ones. Plasma slightly enhanced germination rate and considerably influenced growth parameters. Seedling length and weight are significantly higher than those of untreated seeds. The influence of plasma exposure is more visible on the plant roots, which are substantially longer and more branched. An increase in weight of 20–40% was observed for the plants grown from treated seeds as compared to the control ones. The best results are obtained for relatively short plasma exposure, while too long treatment appears to be detrimental to the seeds.